Fenofibrate Improves Insulin Resistance and Hepatic Steatosis and Regulates the Let-7/SERCA2b Axis in High-Fat Diet-Induced Non-Alcoholic Fatty Liver Disease Mice - Zhang, Dan; Niu, Shanzhuang; Ma, Yicheng; Chen, Hang; Wen, Yu; Li, Mingke; Zhou, Bo; Deng, Yi; Shi, Chunjing; Pu, Guangyu; Yang, Meng; Wang, Xianmei; et al. (Frontiers in Pharmacology, 2022)
Fenofibrate is widely used in clinical therapy to effectively ameliorate the development of non-alcoholic fatty liver disease (NAFLD); however, its specific molecular mechanism of action remains largely unknown. MicroRNAs (miRNAs) are key mediators in regulating endoplasmic reticulum (ER) stress during NAFLD, and the deregulation of miRNAs has been demonstrated in NAFLD pathophysiology. The present study aimed to identify whether fenofibrate could influence miRNA expression in NAFLD and investigate the specific mechanism of action of fenofibrate in lipid metabolism disorder-associated diseases. We found that fenofibrate alleviated ER stress and increased the levels of SERCA2b, which serves as a regulator of ER stress. Additionally, the levels of let-7 miRNA were regulated by fenofibrate; let-7 was found to target the 3′ untranslated region of SERCA2b. The present data suggest that the protective effects of fenofibrate against insulin resistance and its suppressive activity against excessive hepatic lipid accumulation may be related to the alteration of the let-7/SERCA2b axis and alleviation of ER stress.